2022
DOI: 10.1186/s12882-022-02966-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events and mortality in chronic kidney disease in primary care patients with previous type 2 diabetes and/or hypertension. A population-based epidemiological study (KIDNEES)

Abstract: Background Chronic Kidney Disease (CKD), Type 2 Diabetes (T2D) and Hypertension (HTN) are frequently associated with adverse outcomes. We aimed to estimate the impact of a prior diagnosis of T2D and/or HTN on clinical characteristics, cardiovascular events (CVE) and all-cause mortality (ACM) of patients with CKD. Methods We conducted a retrospective cohort study based on primary care electronic health records of people without atherosclerotic cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…In our study, mean age was 68–72, years, median eGFR 44 ml/min/1.73 m 2 , and median UACR 110–339 mg/g. Previous studies performed in European populations of patients with CKD and T2D have shown a similar clinical profile to that observed in our study [ 27 , 28 ]. In the FIDELITY pooled analysis, which combined data from the FIGARO and FIDELIO trials, mean age was 64.8 years, 30.2% of patients were female, baseline eGFR was 57.6 ml/min/1.73 m 2 , and baseline UACR 515 mg/g [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, mean age was 68–72, years, median eGFR 44 ml/min/1.73 m 2 , and median UACR 110–339 mg/g. Previous studies performed in European populations of patients with CKD and T2D have shown a similar clinical profile to that observed in our study [ 27 , 28 ]. In the FIDELITY pooled analysis, which combined data from the FIGARO and FIDELIO trials, mean age was 64.8 years, 30.2% of patients were female, baseline eGFR was 57.6 ml/min/1.73 m 2 , and baseline UACR 515 mg/g [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Compared with the overall population, patients taking concomitant SGLT2i had lower eGFR and UACR. This proportion of ACEi and ARB use is similar to that observed in prior observational studies of patients with CKD and T2D [ 28–30 ]. In FIDELITY, almost all patients were receiving RAS inhibitors, 7% SGLT2i and GLP-1RA, and the CV and renal benefits of finerenone were independent of treatment with SGLT2i and GLP-1RA [ 10 , 31 ].…”
Section: Discussionsupporting
confidence: 86%